Fiber product treatment agent composition
Patent Information
- Application Number
- JP2022101899
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-06-24
AI Technical Summary
Textile product treatment agents containing anionic surfactants cause wrinkles and excessive foaming during drying, necessitating additional steps like steam treatment or ironing to remove wrinkles and managing foam overflow.
A textile treatment agent composition comprising sulfosuccinic acid esters or salts with hydrocarbon groups of 5 to 18 carbon atoms, combined with cationic and nonionic polymers, reduces foaming and suppresses wrinkle formation during drying.
The composition effectively minimizes foaming and reduces wrinkle formation in textile products, particularly when dried in a dryer, enhancing processing efficiency and reducing environmental impact.
Abstract
Description
[Technical field]
[0001] The present invention relates to a textile product treatment composition and a method for treating textile products. [Background technology]
[0002] 2. Description of the Related Art Anionic surfactants such as alkylbenzenesulfonates, alkyl sulfates, polyoxyethylene alkyl ether sulfates, internal olefin sulfonates, and sulfosuccinates have conventionally been used as cleaning components for household and industrial use.
[0003] Patent Document 1 discloses a cleaning composition comprising a specific anionic surfactant (A), at least one amphoteric surfactant (B), and at least one nonionic surfactant (C). Patent Document 2 discloses a liquid detergent composition for textile products, which contains predetermined amounts of (A) an internal olefin sulfonate, (B) a specified organic solvent, (C) a specified water-soluble polyhydric alcohol, and water, and the mass ratio (B) / (C) of the content of component (B) to the content of component (C) is 0.1 or more and 10 or less. Patent Document 3 discloses a liquid detergent composition for fabric products, which contains predetermined amounts of (a) a polysaccharide polymer having a cationic group, (b) an aromatic sulfonate having a branched alkyl group having from 3 to 8 carbon atoms, and (c) one or more surfactants selected from anionic surfactants and nonionic surfactants. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-151360 A [Patent Document 2] Patent Publication No. 2021-088703 [Patent Document 3] JP 2020-105422 A Summary of the Invention [Problem to be solved by the invention]
[0005] While textile product treatment compositions containing an anionic surfactant as a main ingredient exhibit excellent cleaning performance, they tend to cause wrinkles in the finished textile products after drying. In particular, when textile products are dried in a clothes dryer, wrinkles are formed significantly, and wrinkles must be removed by steam treatment or ironing after drying. In addition, since anionic surfactants have excellent foaming properties, foam control is also an important factor. For example, depending on the method of treating textile products, foam control may be required to prevent the foam formed during treatment from overflowing and excessive foam formation. In addition, if the amount of foam formed during treatment is reduced, the rinsing time and the amount of rinsing water can be reduced, so that the foaming property of the textile product treatment composition is required to be suppressed from the viewpoint of shortening treatment time and reducing environmental load. The present invention provides a textile product treatment composition which suppresses foaming of a treatment liquid used to treat a textile product and has excellent performance in suppressing wrinkles formed on the textile product during a drying process after the textile product is treated. [Means for solving the problem]
[0006] The present invention relates to a textile product treatment composition comprising the following components (a) and (b): Component (a): a sulfosuccinic acid ester or a salt thereof having a hydrocarbon group having 5 to 18 carbon atoms Component (b): one or more polymers selected from the following components (b1) and (b2): Component (b1): cationic polymer (b2) component: nonionic polymer
[0007] The present invention also relates to a method for treating a textile product, which comprises treating the textile product with a treatment liquid obtained by mixing the above-mentioned component (a), component (b) and water, and then drying the textile product. Effect of the Invention
[0008] According to the present invention, there is provided a textile product treatment composition which suppresses foaming of a treatment liquid used to treat a textile product and has excellent performance in inhibiting wrinkles formed on the textile product during the drying process after the textile product is treated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention has been made possible by the discovery that, by using the above-mentioned components (a) and (b), it is possible to obtain a textile product treatment composition and a textile product treatment method which suppress foaming during textile product treatment and further reduce wrinkles formed in the textile product during the drying process for drying a wet textile product, particularly during the drying process using a dryer. The mechanism by which the textile product treatment composition of the present invention suppresses foaming during treatment and the mechanism by which the textile product is prevented from forming wrinkles when dried are not clear, but the following is presumed. First, it is presumed that the textile product treatment composition of the present invention suppresses foaming in an aqueous solution by forming a hydrated solid in the aqueous solution containing the treatment composition, and that the combined use of components (a) and (b) promotes the formation of a hydrated solid on the fiber surface, thereby reducing wrinkles formed on the textile product during the drying process. It is believed that this provides a textile product treatment composition and a textile product treatment method that simultaneously suppresses foaming of the treatment liquid used to treat textile products and reduces wrinkles that form on the textile products during the drying process after treatment of the textile products, particularly the drying process in a dryer. The textile product cleaning composition and textile product treating method of the present invention are not limited to the above-mentioned mechanism of action.
[0010] <Textile product treatment composition> The textile product treatment composition of the present invention contains the following components (a) and (b): Component (a): a sulfosuccinic acid ester or a salt thereof having a hydrocarbon group having 5 to 18 carbon atoms Component (b): one or more polymers selected from the following components (b1) and (b2): Component (b1): cationic polymer (b2) component: nonionic polymer
[0011] The textile product treatment composition of the present invention may be one or more compositions selected from a textile product detergent composition for cleaning textile products, a textile product finishing composition for improving the finish of textile products after treatment, a textile product softener composition for imparting softness to textile products, and a textile product wrinkle inhibitor composition for inhibiting the formation of wrinkles in textile products when the textile products are dried after treatment. From the viewpoints of reducing foaming properties of the treatment liquid for treating a textile product, suppressing wrinkles formed on the textile product, and cleaning properties, the textile product treatment composition of the present invention is preferably a detergent composition for textile products, and more preferably a detergent composition for textile products that is dried in a dryer. In the present invention, wrinkles formed in a textile product are synonymous with twisting, wear, and loss of shape of the textile product. In the present invention, the term "defoaming property" includes the suppression of foaming of a treatment liquid containing the textile product treatment composition of the present invention, and the rapid disappearance of foam formed in the treatment liquid.
[0012] <Component (a)> The component (a) is a sulfosuccinate ester or a salt thereof having a hydrocarbon group having 5 to 18 carbon atoms. The component (a) may be a sulfosuccinate monoester or a sulfosuccinate diester, and is preferably a sulfosuccinate diester or a salt thereof. The textile product treatment composition of the present invention may contain one or more types of component (a). Examples of the hydrocarbon group of component (a) include alkyl groups and alkenyl groups, and from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, alkyl groups are preferred. From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the number of carbon atoms of the hydrocarbon group of component (a) is independently 5 or more, preferably 6 or more, more preferably 8 or more, and even more preferably 10 or more, and from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, it is 18 or less, preferably 15 or less, and more preferably 12 or less. In addition, the hydrocarbon group of component (a) may be either a straight chain or a branched chain, and from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, it is preferable that the hydrocarbon group has a branched chain.
[0013] From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the component (a) is preferably a sulfosuccinic acid diester having two hydrocarbon groups having 5 to 18 carbon atoms or a salt thereof, and examples thereof include compounds represented by the following general formula (a1).
[0014] [ka] [In the formula, R 1 , R 2 are each a hydrocarbon group having 5 to 18 carbon atoms, 1 O, A 2 Each O is an alkyleneoxy group having 2 to 4 carbon atoms, x1 and x2 are the average number of moles added, each being a number of 0 to 10, and M is a cation.
[0015] In general formula (a1), R 1 and R 2 may be the same or different, and each is a hydrocarbon group having 5 to 18 carbon atoms. Examples of the hydrocarbon group include an alkyl group and an alkenyl group. From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the alkyl group is preferred.
[0016] In general formula (a1), R 1 and R 2 The number of carbon atoms in the hydrocarbon group is, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, 5 or more, preferably 6 or more, more preferably 8 or more, and even more preferably 10 or more, and, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, 18 or less, preferably 15 or less, and more preferably 12 or less.
[0017] In general formula (a1), R 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the total number of carbon atoms in R is preferably 12 or more, more preferably 16 or more, even more preferably 20 or more, and preferably 30 or less, more preferably 24 or less. 1 and R 2In the case where two or more compounds having different total carbon numbers are contained, (a1) R as the whole component 1 and R 2 The total number of carbon atoms in each compound is R 1 and R 2 represents the molar average of the total carbon number.
[0018] In general formula (a1), R 1 and R 2 The hydrocarbon group of R may be either a straight chain or a branched chain, but from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, it is preferable that the hydrocarbon group R has a branched chain. 1 and R 2 From the viewpoint of antifoaming properties, the branched hydrocarbon group preferably has a side chain having 2 or more carbon atoms, more preferably has a side chain having 3 or more carbon atoms. The number of carbon atoms in the side chain may be 8 or less, and further 6 or less. 1 and R 2 The longest chain of carbon atoms in the hydrocarbon group is called the main chain, with the carbon atom bonded to the oxygen atom (O) in the formula as the first carbon atom. The number of carbon atoms in the main chain is expressed as X(R 1 and R 2 has 5 or more carbon atoms, so X has 3 or more carbon atoms), each of the hydrocarbon groups bonded to any of the 1st to X-1th carbon atoms of the main chain is called a side chain. In general formula (a1), R 1 and R 2 The hydrocarbon group may be either saturated or unsaturated. In general formula (a1), R 1 and R 2 At least one of them preferably has a branched structure. In general formula (a1), R 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, it is more preferable that the hydrocarbon group contains a saturated branched chain hydrocarbon group. Also, R 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the hydrocarbon group may be a group derived from Guerbet alcohol.
[0019] R in general formula (a1)1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, each of the above independently represents preferably a branched chain alkyl group having from 8 to 12 carbon atoms, more preferably a branched chain alkyl group having from 8 to 10 carbon atoms, and even more preferably a branched chain alkyl group having 10 carbon atoms.
[0020] In the present invention, a hydrocarbon residue obtained by removing a hydroxyl group from a secondary alcohol is included in a branched chain hydrocarbon group such as a branched chain alkyl group. R 1 and R 2 are each a branched chain alkyl group having 8 to 12 carbon atoms, the total number of carbon atoms constituting the side chains may be the same or different, and from the viewpoint of antifoaming property, is preferably 1 or more, more preferably 2 or more, and is preferably 4 or less, more preferably 3 or less, and even more preferably 3. In the present invention, the total number of carbon atoms constituting the side chains refers to the total number of carbon atoms in all side chains other than the main chain in one branched-chain alkyl group, and when there are multiple side chains, it refers to the total number of carbon atoms in all of those side chains.
[0021] R 1 and R 2 The number of side chains of R may be the same or different, and from the viewpoint of antifoaming property and suppression of wrinkle formation during drying, is 1 or more, and preferably 3 or less, more preferably 2 or less. 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the number of side chains of each is preferably 1. In the present invention, the number of side chains refers to the number of side chains branched from the main chain, and the number of side chains does not change even if the side chain has a side chain branched from the side chain. However, although the side chain may have a side chain branched from the side chain, it is preferable that the side chain is a straight chain from the viewpoint of defoaming property and suppression of wrinkle formation during drying.
[0022] R 1 and R 2 are each independently a branched chain alkyl group having from 8 to 12 carbon atoms, R 1 and R2 The number of branched carbon atoms in R may be the same or different, and from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, is 1 or more, and preferably 3 or less, more preferably 2 or less. 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the number of branched carbons is preferably 1. In the present invention, the number of branched carbons refers to the total number of tertiary carbon atoms and quaternary carbon atoms in the branched alkyl group.
[0023] R 1 and R 2 A more preferred embodiment of the above, from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, is a branched-chain alkyl group having 8 to 12 carbon atoms, in which the number of carbon atoms in the main chain is independently 6 to 8, the number of carbon atoms constituting the side chains is independently preferably 1 or more, more preferably 2 or more, and preferably 4 or less, more preferably 3 or less, and even more preferably 3, and the number of side chains is independently preferably 3 or less, more preferably 2 or less, and even more preferably 1. R 1 and R 2 From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the branched alkyl group is preferably selected from a branched octyl group, a branched decyl group, and a branched dodecyl group, and a branched decyl group is more preferable. Examples of the branched octyl group include a 2-ethylhexyl group. Examples of the branched decyl group include a 2-propylheptyl group and a group derived from decyl alcohol manufactured by KH Neochem Co., Ltd., and a 2-propylheptyl group is preferable. Examples of the branched dodecyl group include a 2-butyloctyl group.
[0024] In general formula (a1), R 1 The hydrocarbon group and R 2 The hydrocarbon groups in R may be the same or different. 1 The hydrocarbon group and R 2 In the case where the hydrocarbon groups in R are the same, this is preferable from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying. 1 The number of carbon atoms and R 2 The carbon numbers of R may be the same or different.1 The number of carbon atoms and R 2 The case where the carbon numbers of and are the same is preferable from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0025] In general formula (a1), R 1 and R 2 The degree of branching of the hydrocarbon group defined by the following formula is preferably 0.3 or less, more preferably 0.2 or less, even more preferably 0.1 or less, and still more preferably 0.08 or less, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, and is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.04 or more, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying. Degree of branching = (R 1 and R 2 (total number of terminal methyl groups)-2) / (R 1 and R 2 (total number of carbon atoms) The branching degree is, 1 It is an average value that can be measured using H-NMR.
[0026] In general formula (a1), A 1 O, A 2 O is an alkyleneoxy group having 2 to 4 carbon atoms, preferably having 2 or 3 carbon atoms, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying. 1 O, A 2 Each of these represents the average number of moles of O added, and from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, it is preferably a number of 6 or less, more preferably a number of 4 or less, even more preferably a number of 2 or less, and still more preferably 0.
[0027] In the general formula (a1), M is a cation. M is preferably a cation other than a hydrogen ion. Examples of M include alkali metal ions such as lithium ion, sodium ion, and potassium ion, alkaline earth metal ions such as magnesium ion, calcium ion, and barium ion, and organic ammonium ions such as triethanolammonium ion, diethanolammonium ion, monoethanolammonium ion, trimethylammonium ion, and monomethylammonium ion. From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, M is preferably an alkali metal ion or an alkanol ammonium ion, more preferably a sodium ion, a potassium ion, a triethanol ammonium ion, a diethanol ammonium ion or a monoethanol ammonium ion, and still more preferably a sodium ion.
[0028] <(b) Component> The component (b) is one or more polymers selected from the components (b1) and (b2). From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the component (b) preferably contains one or more polymers selected from the component (b1).
[0029] <(b1) component> The component (b1) is a cationic polymer. In this specification, the term "cationic polymer" refers to a polymer that has cationic groups and has a cationic charge as a whole, and the cationic group refers to a cationic group or a group that can be ionized to become a cationic group. Specific examples of the cationic group include a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary ammonium group.
[0030] Examples of the cationic polymer of component (b1), from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, include polyethyleneimine; cationic polygalactomannans such as cationic guar gum, cationic tara gum, and cationic locust bean gum; cationic cellulose; cationic hydroxyalkylcelluloses such as cationic hydroxyethyl cellulose and cationic hydroxypropyl cellulose; cationic starch; cationic polyvinyl alcohol; Quaternized dialkylaminoalkyl (meth)acrylate polymers such as vinylpyrrolidone / N,N-dimethylaminoethyl diethyl methacrylate sulfate copolymer, N,N-dimethylaminoethyl diethyl methacrylate sulfate / N,N-dimethylacrylamide / polyethylene glycol dimethacrylate copolymer; Diallyl quaternary ammonium salt polymers such as polydiallyl dimethyl ammonium chloride, diallyl dimethyl ammonium chloride / acrylic acid copolymer, diallyl dimethyl ammonium chloride / acrylamide copolymer, and diallyl dimethyl ammonium chloride / acrylic acid / acrylamide copolymer; vinylimidazolium trichloride / vinylpyrrolidone copolymer; vinylpyrrolidone / alkylaminoalkyl(meth)acrylate copolymer; vinylpyrrolidone / alkylaminoalkyl(meth)acrylate / vinylcaprolactam copolymer; vinylpyrrolidone / (meth)acrylamidopropyl trimethylammonium chloride copolymer; alkylacrylamide / (meth)acrylate / alkylaminoalkylacrylamide / polyethylene glycol(meth)acrylate copolymer; adipic acid / dimethylaminohydroxypropylethylenetriamine copolymer; and Examples of the cationic polymers include those described in JP-A-53-139734 and JP-A-60-36407, and one or more of these can be used. Among these, from the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, one or more selected from the group consisting of polyethyleneimine, cationized polygalactomannan, cellulose-based cationic polymers (e.g., cationic cellulose, cationized hydroxyalkyl cellulose, alkylated cationized hydroxyalkyl cellulose, etc.), quaternized dialkylaminoalkyl (meth)acrylate polymers, and diallyl quaternary ammonium salt polymers are preferred, one or more selected from the group consisting of polyethyleneimine, cationized guar gum, cationized hydroxyalkyl cellulose, alkylated cationized hydroxyalkyl cellulose, and quaternized dialkylaminoalkyl (meth)acrylate polymers are more preferred, one or more selected from the group consisting of cationized hydroxyalkyl cellulose and alkylated cationized hydroxyalkyl cellulose are even more preferred, and one or more selected from the group consisting of alkylated cationized hydroxyalkyl cellulose are even more preferred.
[0031] From the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, the (b1) component may be a polysaccharide polymer having a cationic group. The (b1) component may be a polysaccharide polymer in which a cationic group is bound, directly or via a linking group, to a group obtained by removing a hydrogen atom from a hydroxyl group of a polysaccharide or a derivative thereof, which is a precursor compound of the (b1) component. Note that the above phrase "a cationic group is bound, directly or via a linking group, to a group obtained by removing a hydrogen atom from a hydroxyl group of a polysaccharide or a derivative thereof" does not include a bonding mode in which a cationic atom of the cationic group, for example, a nitrogen cation, is directly and covalently bonded to a group obtained by removing a hydrogen atom from a hydroxyl group of a polysaccharide or a derivative thereof, i.e., an oxygen atom.
[0032] The polysaccharide may, for example, be one or more polysaccharides selected from cellulose, guar gum, or starch.
[0033] When the component (b1) is a polysaccharide polymer having a cationic group, a polysaccharide polymer can be used as a precursor compound to obtain it. That is, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the component (b1) may be a derivative of a polysaccharide polymer. The polysaccharide polymer, which is a precursor compound of the component (b1), may be a polysaccharide polymer in which some or all of the hydrogen atoms of the hydroxyl groups of the polysaccharide are substituted with a hydroxyalkyl group having 1 to 4 carbon atoms (hereinafter, also referred to as a hydroxyalkyl substituted product) from the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying. The hydroxyalkyl group having 1 to 4 carbon atoms is preferably a hydroxyalkyl group having 2 to 4 carbon atoms from the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying. The hydroxyalkyl group having 2 to 4 carbon atoms may be, for example, one or more groups selected from a hydroxyethyl group, a hydroxypropyl group, and a hydroxybutyl group, and preferably one or more groups selected from a hydroxyethyl group and a hydroxypropyl group, from the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying. The component (b1) may be a compound in which a cationic group is introduced into a polysaccharide or polysaccharide polymer selected from one or more polysaccharides selected from cellulose, guar gum, and starch, or hydroxyalkyl substituted products thereof, from the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying.
[0034] The degree of substitution of the cationic group in the polysaccharide polymer having a cationic group, which is component (b1), is preferably 0.001 or more, more preferably 0.005 or more, even more preferably 0.01 or more, from the viewpoints of defoaming properties and suppression of wrinkle formation during drying, and is preferably 1 or less, more preferably 0.7 or less, even more preferably 0.5 or less.
[0035] From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the polysaccharide polymer having a cationic group can be, for example, a polysaccharide or a derivative thereof, which is a precursor compound of component (b1), preferably a polysaccharide polymer in which a cationic group is bonded to a group obtained by removing a hydrogen atom from a hydroxyl group possessed by the hydroxyalkyl substituent, via a linking group, an alkylene group having 1 to 4 carbon atoms which may contain a hydroxyl group [hereinafter referred to as linking group (1)]. The cationic group is preferably a group containing a nitrogen cation, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, and more preferably a quaternary ammonium group, from the viewpoint of easily solving the problems of the present invention through interaction with component (a).
[0036] The linking group (1) is an alkylene group having 1 to 4 carbon atoms which may contain a hydroxyl group, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying. The alkylene group having 1 to 4 carbon atoms may be one or more alkylene groups selected from linear alkylene groups having 1 to 4 carbon atoms which may contain a hydroxyl group and branched alkylene groups having 3 to 4 carbon atoms which may contain a hydroxyl group, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0037] When the cationic group is a quaternary ammonium group, from the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying, the three hydrocarbon groups other than the linking group (1) bonded to the quaternary ammonium group each independently include a straight-chain or branched-chain hydrocarbon group having 1 to 4 carbon atoms. From the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying, examples of the straight-chain hydrocarbon group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, and an n-butyl group. From the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying, examples of the branched-chain hydrocarbon group having 3 to 4 carbon atoms include an isopropyl group, a sec-butyl group, a tert-butyl group, and an isobutyl group. From the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying, examples of the straight-chain hydrocarbon group having 1 to 4 carbon atoms include a methyl group or an ethyl group. The counter ion of the quaternary ammonium group may be one or more counter ions selected from alkyl sulfate ions having 1 to 3 carbon atoms, sulfate ions, phosphate ions, fatty acid ions having 1 to 3 carbon atoms, and halide ions from the viewpoint of antifoaming properties and wrinkle formation suppression during drying. Among these, from the viewpoint of antifoaming properties and wrinkle formation suppression during drying, preferably one or more selected from alkyl sulfate ions having 1 to 3 carbon atoms, sulfate ions, and halide ions, more preferably halide ions. Examples of halide ions include fluoride ions, chloride ions, bromide ions, and iodide ions. From the viewpoint of antifoaming properties and wrinkle formation suppression during drying, preferably one or more selected from chloride ions and bromide ions, more preferably chloride ions. The counter ion may be one type alone or two or more types.
[0038] From the viewpoint of antifoaming properties and wrinkle formation suppression during drying, it is preferable to select the content of cationic groups in the (b1) component. The content of cationic groups in the (b1) component, which is a polysaccharide polymer having cationic groups, is calculated by replacing the cationic groups with nitrogen atoms. That is, the content of cationic groups in the (b1) component can be determined by the content ratio of nitrogen atoms in the (b1) component. From the viewpoint of antifoaming properties and wrinkle formation suppression during drying, the content of nitrogen atoms in the (b1) component is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 4% by mass or less, even more preferably 3% by mass or less, even more preferably 2% by mass or less, even more preferably 1% by mass or less, even more preferably 0.6% by mass or less, and from the viewpoint of antifoaming properties and wrinkle formation suppression during drying, it is preferably 0.05% by mass or more, more preferably 0.1% by mass or more. The nitrogen atom content in component (b1) can be determined by the method described in detail below in <Method of measuring nitrogen content and degree of alkyl substitution in component (b1)>.
[0039] The polysaccharide polymer having a cationic group, which is the component (b1), may be a polysaccharide polymer having a cationic group to which a hydrocarbon group having 1 to 18 carbon atoms is further bonded, either directly or via a linking group [hereinafter referred to as linking group (2)], from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0040] From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the linking group (2) may be one or more groups selected from an alkyleneoxy group having 1 to 3 carbon atoms which may have a hydroxyl group, a polyoxyalkylene group in which the alkylene group has 1 to 3 carbon atoms, a carbonyl group, a carbonyloxy group, and an oxycarbonyl group. One linking group (2) may be one type of the linking group or a combination of two or more types. The linking group contained in the polysaccharide polymer may be one type or two or more types. In the present invention, when the hydrocarbon group is linked to the oxygen atom of the linking group (2), the carbon number of the hydrocarbon group of the component (b1) represents the carbon number of the hydrocarbon group bonded to the oxygen atom. When the hydrocarbon group is linked via a carbonyl group, an acyl group is bonded to the hydrocarbon group, and in this case, the carbon number of the hydrocarbon group of the component (b1) represents the carbon number of the acyl group. When the hydrocarbon group is linked via a carbonyloxy group and an oxycarbonyl group, the carbon numbers of the hydrocarbon group and the acyl group are included. When a 1,2-epoxyalkane is used to introduce a hydrocarbon group into a polysaccharide or polysaccharide polymer, the carbon number of the aliphatic hydrocarbon group bonded to the ether group generated from the epoxy group is represented. The epoxy group portion becomes the linking group (2). For example, when a hydrocarbon group is introduced into a polysaccharide or polysaccharide polymer using 1,2-epoxytetradecane, the number of carbons of the hydrocarbon group is 12. That is, an oxyethylene group, which is the linking group (1), is bonded to a hydroxyl group of a polysaccharide or polysaccharide polymer, and an alkyl group having 12 carbon atoms (dodecyl group) is bonded via the linking group. The same applies when an alkyl glycidyl ether is used.
[0041] Among the polysaccharide polymers having a cationic group and a hydrocarbon group having from 1 to 18 carbon atoms, from the viewpoints of antifoaming property and suppression of wrinkle formation during drying, there may be mentioned polysaccharide polymers having a cationic group, to which a hydrocarbon group having from 1 to 18 carbon atoms is bonded, directly or via a linking group (2), preferably via a linking group (2), to oxygen atoms obtained by removing hydrogen atoms from some or all of the hydroxyl groups of the polysaccharide polymer having a cationic group.
[0042] From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the number of carbon atoms in the hydrocarbon group having 1 to 18 carbon atoms is preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, still more preferably 8 or more, still more preferably 10 or more, still more preferably 12 or more, and preferably 16 or less, more preferably 14 or less. From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the hydrocarbon group is preferably an aliphatic hydrocarbon group.
[0043] The degree of substitution of the hydrocarbon group having 1 to 18 carbon atoms in the polysaccharide polymer having a cationic group and a hydrocarbon group having 1 to 18 carbon atoms, which is component (b1), is preferably 0.0001 or more, more preferably 0.001 or more, even more preferably 0.005 or more, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, and is preferably 0.4 or less, more preferably 0.2 or less, even more preferably 0.1 or less, still more preferably 0.08 or less, and even more preferably 0.06 or less, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying. The degree of substitution of the hydrocarbon group having from 1 to 18 carbon atoms in the component (b1) can be determined by the method described in detail below in <Method of measuring the nitrogen content and alkyl substitution degree of the component (b1)>.
[0044] The weight average molecular weight of the polysaccharide or its derivative, which is the precursor compound of the component (b1) of the present invention, is preferably 1,000 or more, more preferably 10,000 or more, even more preferably 30,000 or more, even more preferably 50,000 or more, even more preferably 70,000 or more, even more preferably 100,000 or more, even more preferably 300,000 or more, even more preferably 500,000 or more, and from the viewpoint of the antifoaming property and the inhibition of the formation of wrinkles when drying, it is preferably 3 million or less, more preferably 2 million or less, even more preferably 1 million or less. The weight average molecular weight of this precursor compound can be calculated in terms of polyethylene glycol by GPC (gel permeation chromatography).
[0045] The weight average molecular weight of the (b1) component is preferably 1,000 or more, more preferably 10,000 or more, even more preferably 30,000 or more, still more preferably 50,000 or more, still more preferably 70,000 or more, still more preferably 100,000 or more, still more preferably 300,000 or more, still more preferably 500,000 or more, and from the viewpoint of the antifoaming property and the inhibition of the formation of wrinkles during drying, it is preferably 3 million or less, more preferably 2 million or less, and still more preferably 1 million or less. This weight average molecular weight can be calculated in terms of polyethylene glycol by GPC (gel permeation chromatography).
[0046] The weight average molecular weight of the precursor compound of the component (b1) and the component (b1) is calculated in terms of polyethylene glycol by GPC (gel permeation chromatography) under the following measurement conditions. Column: TSKgel α-M Eluent: 50mmol / L LiBr, 1% CH3COOH, ethanol / water = 3 / 7 ·Temperature: 40℃ ·Flow rate: 0.6mL / min
[0047] <Method for measuring the nitrogen content and alkyl substitution degree of component (b1)> The nitrogen content and the degree of alkyl group substitution of the polysaccharide derivative, which is the component (b1), are measured by the following method. Pretreatment of polysaccharide derivatives After dissolving 1 g of the polysaccharide derivative in 100 g of water, the aqueous solution is placed in a dialysis membrane (Spectrapore, molecular weight cutoff 1000) and dialyzed for 2 days. The resulting aqueous solution is freeze-dried using a freeze dryer (eyela, FDU1100) to obtain a pretreated polysaccharide derivative.
[0048] Calculation of cationic substrate amount by Kjeldahl method 200 mg of the polysaccharide derivative pretreated by the above method is weighed out, 10 mL of concentrated sulfuric acid and one Kjeldahl tablet (Merck) are added, and the sample is subjected to thermal decomposition in a Kjeldahl digestion apparatus (BUCHI, K-432). After completion of the decomposition, 30 mL of ion-exchanged water is added to the sample, and the nitrogen content (mass%) of the sample is determined using an automatic Kjeldahl distillation apparatus (BUCHI, K-370), to calculate the mass of the cationic group.
[0049] Calculation of the mass of hydrocarbon groups (alkyl groups) by the Zeisel method 200 mg of the polysaccharide derivative pretreated by the above method and 220 mg of adipic acid are weighed out in a 10 mL vial (Mighty Vial No. 3), 3 mL of internal standard solution (tetradecane / o-xylene = 1 / 25 (v / v)) and 3 mL of hydroiodic acid are added, and the vial is sealed. In addition, 2.4 mg or 9 mg of 1-iodododecane is added instead of the polysaccharide derivative to prepare a sample for the calibration curve. Each sample is heated at 160 °C for 2 hours using a block heater (PIERCE, Reacti-Therm III Heating / Stirring module) while stirring with a stirrer tip. After cooling the sample, the upper layer (o-xylene layer) is collected and analyzed by gas chromatography (GC) (Shimadzu Corporation, QD2010plus) under the following conditions. ·GC analysis conditions Column: Agilent HP-1 (length: 30 m, liquid phase film thickness: 0.25 μL, inner diameter: 32 mm) Split ratio: 20 Column temperature: 100℃(2min)→10℃ / min→300℃(15min) Injector temperature: 300℃ Detector: HID Detector temperature: 330℃ Injection volume: 2μL The mass of the alkyl group in the sample is determined from the amount of 1-iodododecane detected by GC.
[0050] Commercially available cationic polymers that can be used as the component (b1) from the viewpoints of defoaming properties and suppression of wrinkle formation during drying include, for example, the following. (cationized guar gum) JAGUAR Excel, JAGUAR C-17, JAGUAR C-14-S (all from Solvay (Novecare)), etc. (cationized tara gum) Catinal CTR-100 (Toho Chemical Industry Co., Ltd.), etc. (cationized locust bean gum) Catinal CLB-100 (Toho Chemical Industry Co., Ltd.), etc. (cationized hydroxyethyl cellulose) Polyquaternium-10 (o-[2-hydroxy-3-(trimethylammonio)propyl]hydroxyethylcellulose chloride): UCARE POLYMER JR-30M, UCARE POLYMER JR-400 (both from The Dow Chemical Company), Poise C-60H, Poise C-150L (both from Kao Corporation), etc. Polyquaternium-67: SoftCAT (Dow Chemical Company), etc. (cationized hydroxypropyl cellulose) SOFCARE C-HP2W (Kao Corporation), etc. (cationized polyvinyl alcohol) Gohsenex K-434 (Nippon Synthetic Chemical Industry Co., Ltd.), CM318 (Kuraray Co., Ltd.), etc. (Vinylpyrrolidone / N,N-Dimethylaminoethyl Methacrylate Diethyl Sulfate Copolymer) Polyquaternium-11: Gafcut 734, Gafcut 755N (both from ISP Japan), etc. (N,N-Dimethylaminoethyl Methacrylate Diethyl Sulfate / N,N-Dimethylacrylamide / Polyethylene Glycol Dimethacrylate Copolymer) Polyquaternium-52: SOFCARE KG-101E, SOFCARE KG-101W-E (both from Kao Corporation), etc. (Polydiallyldimethylammonium chloride) Polyquaternium-6: MERQUAT100 (Lubrizol), etc. (Diallyldimethylammonium chloride / acrylic acid copolymer) Polyquaternium-22: MERQUAT280, MERQUAT295 (both from Lubrizol), etc. (Diallyldimethylammonium chloride / acrylamide copolymer) Polyquaternium-7: MERQUAT550 (Lubrizol), etc. (Diallyldimethylammonium chloride / acrylic acid / acrylamide polymer) Polyquaternium-39: MERQUAT3331PR (Lubrizol), etc.
[0051] <(b2) component> The component (b2) is a nonionic polymer. The textile product treatment composition of the present invention may contain one or more types of the component (b2).
[0052] Examples of the nonionic polymer of component (b2), from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, include polymers having structural units derived from nonionic monomers, water-soluble polysaccharides (cellulose-based, gum-based, starch-based, etc.) and their derivatives. Examples of the nonionic monomer in the nonionic polymer include ethylene glycol, propylene glycol, glycerin, diols or diisocyanates having an aliphatic hydrocarbon group, and amines, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0053] From the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, specific examples of the component (b2) include polyurethane polyurea, cellulose-based polymers such as hydroxyalkyl cellulose and alkylated hydroxyalkyl cellulose, polyethylene glycol, polypropylene glycol, polyglycerin, pullulan, guar gum, and poly(2-alkyl-2-oxazoline). From the viewpoint of suppressing wrinkle formation during drying, the component (b2) is preferably one or more selected from the group consisting of hydroxyalkyl celluloses and alkylated hydroxyalkyl celluloses, more preferably one or more selected from the group consisting of alkylated hydroxyalkyl celluloses, and more preferably one selected from the group consisting of alkylated hydroxyethyl celluloses.
[0054] From the viewpoint of antifoaming properties and wrinkle suppression during drying, the component (b2) may be a nonionic polysaccharide polymer that is a polysaccharide or a derivative thereof. The polysaccharide may be, for example, one or more polysaccharides selected from cellulose, guar gum, and starch. From the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, examples of the nonionic polysaccharide polymer as component (b2) include polysaccharide polymers in which some or all of the hydrogen atoms of the hydroxyl groups of the polysaccharide are substituted with hydroxyalkyl groups having from 1 to 4 carbon atoms (hereinafter also referred to as hydroxyalkyl substitution products). From the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, the hydroxyalkyl groups having from 1 to 4 carbon atoms are preferably hydroxyalkyl groups having from 2 to 4 carbon atoms. From the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, examples of the hydroxyalkyl groups having from 2 to 4 carbon atoms include one or more groups selected from a hydroxyethyl group, a hydroxypropyl group, and a hydroxybutyl group, and one or more groups selected from a hydroxyethyl group and a hydroxypropyl group are preferred.
[0055] From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the nonionic polysaccharide polymer of component (b2) may be a polysaccharide polymer in which a hydrocarbon group having 1 to 18 carbon atoms is further bonded to the polysaccharide or a hydroxyalkyl-substituted polysaccharide, either directly or via the linking group (2).
[0056] From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the number of carbon atoms in the hydrocarbon group having 1 to 18 carbon atoms is preferably 2 or more, more preferably 4 or more, even more preferably 6 or more, still more preferably 8 or more, still more preferably 10 or more, still more preferably 12 or more, and preferably 16 or less, more preferably 14 or less. From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the hydrocarbon group is preferably an aliphatic hydrocarbon group.
[0057] The degree of substitution of the hydrocarbon group having 1 to 18 carbon atoms in the polysaccharide polymer having a hydrocarbon group having 1 to 18 carbon atoms, which is component (b2), is preferably 0.0001 or more, more preferably 0.001 or more, even more preferably 0.005 or more, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying, and is preferably 0.4 or less, more preferably 0.2 or less, even more preferably 0.1 or less, still more preferably 0.08 or less, and even more preferably 0.06 or less, from the viewpoints of anti-foaming properties and inhibition of wrinkle formation during drying. The degree of substitution of the hydrocarbon group having 1 to 18 carbon atoms in the component (b2) can be determined in the same manner as described above for the component (b1).
[0058] Examples of commercially available nonionic polymers that can be used from the viewpoints of antifoaming properties and wrinkle inhibition during drying include polyurethane polyureas such as the BAYCUSAN series (trade name, manufactured by Covestro Japan Co., Ltd.); hydroxyethyl celluloses such as HEC Daicel SE900, HEC Daicel SE850, HEC Daicel SE600, HEC Daicel SE550, and HEC Daicel SE400 (trade names, manufactured by Daicel FineChem Corporation); highly polymerized polyethylene glycols such as Polyox WSRN-12K, HEC Daicel WSRN-60K, and HEC Daicel WSR-301 (trade names, manufactured by Dow Chemical Co., Ltd.); and polyethylene oxides such as PEO-27, PEO-18, PEO-15, and PEO-8 (trade names, manufactured by Sumitomo Seika Chemicals Co., Ltd.).
[0059] From the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, the weight average molecular weight of the (b2) component is preferably 1,000 or more, more preferably 10,000 or more, even more preferably 30,000 or more, still more preferably 100,000 or more, and even more preferably 150,000 or more, and from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, it is preferably 3 million or less, more preferably 1 million or less. This weight average molecular weight can be calculated in terms of polyethylene glycol by GPC (gel permeation chromatography) in the same way as the weight average molecular weight of the (b1) component.
[0060] The component (b2) may be a vinyl-based nonionic polymer having structural units derived from a monomer having a vinyl group. Nonionic monomers that are constituent monomers of vinyl-based nonionic polymers include (meth)acrylates having a hydrocarbon group derived from an aliphatic alcohol having 1 to 22 carbon atoms; N-vinyl-2-pyrrolidone; vinyl alcohol; polyalkylene glycol (meth)acrylates; alkoxypolyalkylene glycol mono(meth)acrylates; (meth)acrylamide; styrene-based monomers such as styrene, α-methylstyrene, and 2-methylstyrene; aromatic group-containing (meth)acrylates such as phenyl (meth)acrylate, benzyl (meth)acrylate, and phenoxyethyl (meth)acrylate; vinyl acetate and its derivatives. Specific examples of vinyl-based nonionic polymers include polyvinyl alcohol, polyvinyl acetal, polyvinylpyrrolidone, copolymers of vinylpyrrolidone with other nonionic monomers such as vinylpyrrolidone / vinyl acetate copolymers, poly N,N-dimethylacrylamide, poly N-vinylacetamide, and poly N-vinylformamide.
[0061] <Composition and other ingredients> The textile product treatment composition of the present invention contains component (a) in an amount of preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more from the viewpoint of defoaming properties, and preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 15% by mass or less, still more preferably 10% by mass or less, and even more preferably 5% by mass or less from the viewpoint of suppressing wrinkle formation during drying. In the definition of the mass of component (a) of the present invention, the mass of component (a) is calculated as the mass of the sodium salt.
[0062] The textile product treatment composition of the present invention contains component (b) in an amount of preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying, and preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and even more preferably 1% by mass or less from the viewpoints of antifoaming properties and inhibition of wrinkle formation during drying. When component (b) contains component (b1), the mass of component (b1) is expressed as the mass converted into the chloride.
[0063] In the textile product treatment composition of the present invention, the mass ratio (a) / (b) of the content of the component (a) to the content of the component (b) is preferably 1 or more, more preferably 2 or more, and even more preferably 4 or more, from the viewpoint of defoaming property, and is preferably 100 or less, more preferably 50 or less, even more preferably 30 or less, and even more preferably 15 or less, from the viewpoint of suppressing wrinkle formation during drying.
[0064] <(c) component> The textile product treatment composition of the present invention may optionally contain (c) an anionic surfactant (excluding component (a)) from the viewpoint of suppressing wrinkle formation during drying. Examples of the anionic surfactant of component (c) from the viewpoint of suppressing wrinkle formation during drying include internal olefin sulfonic acid or its salt, alkylbenzene sulfonic acid or its salt (LAS), polyoxyalkylene alkyl ether sulfate or its salt (AES, APES), alkyl carboxylic acid or its salt, alkyl sulfonic acid or its salt, α-olefin sulfonic acid or its salt, alkyl sulfate ester or its salt (AS), alkyl phosphate ester or its salt, α-sulfo fatty acid methyl ester or its salt (MES), etc. The acid form of the anionic surfactant and its salt may coexist in the composition, or may be added to the composition in the acid form and neutralized with an alkali agent. Hereinafter, "or" is treated similarly.
[0065] From the viewpoint of suppressing wrinkle formation during drying, examples of the salt of component (c) include alkali metal salts such as sodium salts and potassium salts; and alkanolamine salts such as monoethanolamine salts and diethanolamine salts. Of these, alkali metal salts such as sodium salts and potassium salts are preferred.
[0066] From the viewpoint of suppressing wrinkle formation during drying, the component (c) is preferably one or more compounds selected from (c1) internal olefin sulfonic acid and its salts (hereinafter referred to as component (c1)), compounds represented by the following general formula (c2) (hereinafter referred to as component (c2)), compounds represented by general formula (c3) (hereinafter referred to as component (c3)), and compounds represented by general formula (c4) (hereinafter referred to as component (c4)).
[0067] <(c1) component> The internal olefin sulfonate of component (c1) is a sulfonate obtained by sulfonating, neutralizing, and hydrolyzing an internal olefin (an olefin having a double bond inside the olefin chain) having 17 to 24 carbon atoms as a raw material. Such internal olefins include those containing a small amount of so-called alpha olefins (hereinafter also referred to as α-olefins) in which the double bond is located at the first position of the carbon chain. When an internal olefin is sulfonated, β-sultone is quantitatively produced, and a part of the β-sultone is converted to γ-sultone and olefin sulfonic acid, which are further converted to hydroxyalkanesulfonate and olefin sulfonate in the neutralization and hydrolysis process (for example, J. Am. Oil Chem. Soc. 69, 39 (1992)). Here, the hydroxy group of the obtained hydroxyalkanesulfonate is inside the alkane chain, and the double bond of the olefin sulfonate is inside the olefin chain. Furthermore, the obtained product is mainly a mixture of these, and some of the products may contain trace amounts of hydroxyalkanesulfonates having a hydroxy group at the end of the carbon chain or olefinsulfonates having a double bond at the end of the carbon chain. In this specification, these products and mixtures thereof are collectively referred to as internal olefin sulfonate (component (c1)). Furthermore, hydroxyalkanesulfonate is referred to as hydroxy form of internal olefin sulfonate (hereinafter also referred to as HAS form), and olefin sulfonate is referred to as olefin form of internal olefin sulfonate (hereinafter also referred to as IOS form). The mass ratio of the HAS form and the IOS form of the compound in component (c1) can be measured by a high performance liquid chromatography mass spectrometer (hereinafter abbreviated as HPLC-MS). Specifically, the mass ratio can be calculated from the HPLC-MS peak area of component (c1).
[0068] From the viewpoint of suppressing wrinkle formation during drying, examples of the salt of the internal olefin sulfonate include alkali metal salts such as sodium salt and potassium salt, alkaline earth metal salts such as magnesium salt, ammonium salt, and organic amine salts such as monoethanolamine salt, diethanolamine salt, and triethanolamine salt, with alkali metal salts being preferred, and sodium salt being more preferred.
[0069] As is clear from the above production method, the sulfonic acid group of the internal olefin sulfonate of component (c1) is present within the carbon chain of the internal olefin sulfonate, i.e., the olefin chain or alkane chain, and a small amount of some of them may have a sulfonic acid group at the end of the carbon chain.
[0070] In component (c1), the content of internal olefin sulfonate salts in which the sulfonic acid group is present at the 5th position or higher, preferably from the 5th to the 9th position, is, from the viewpoint of suppressing wrinkle formation during drying, preferably 5 mass% or more, more preferably 10 mass% or more, even more preferably 15 mass% or more, still more preferably 20 mass% or more, and is preferably 60 mass% or less, more preferably 55 mass% or less, even more preferably 45 mass% or less, and still more preferably 40 mass% or less.
[0071] In component (c1), the mass ratio of the content of internal olefin sulfonate salts [hereinafter sometimes referred to as (IO-1S)] in which the sulfonic acid group is present at position 2 or more and position 4 or less to the content of internal olefin sulfonate salts [hereinafter sometimes referred to as (IO-2S)] in which the sulfonic acid group is present at position 5 or more, preferably position 5 or more and position 9 or less, (IO-1S) / (IO-2S) is, from the viewpoint of suppressing wrinkle formation during drying, preferably 0.5 or more, more preferably 0.8 or more, even more preferably 1.0 or more, still more preferably 1.5 or more, still more preferably 2 or more, still more preferably 2.5 or more, still more preferably 3 or more, still more preferably 4 or more, and still more preferably 4.5 or more, and from the viewpoint of suppressing wrinkle formation during drying, is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less. The content of each compound having a sulfonic acid group at a different position in the (c1) component can be measured by HPLC-MS. In this specification, the content of each compound having a sulfonic acid group at a different position is determined as a mass ratio based on the HPLC-MS peak area of the compound having a sulfonic acid group at each position in the total HAS body of the (c1) component.
[0072] The content of olefin sulfonate in component (c1) in which a sulfonic acid group is present at position 1 is preferably 10 mass% or less in component (c1) from the viewpoint of suppressing wrinkle formation during drying, more preferably 7 mass% or less, even more preferably 5 mass% or less, and even more preferably 3 mass% or less, and from the viewpoint of suppressing wrinkle formation during drying, is preferably 0.01 mass% or more. The position of the sulfonic acid group in these compounds is a position in the olefin or alkane chain.
[0073] The internal olefin sulfonate may be a mixture of a hydroxyl and an olefin. The mass ratio of the content of the olefin in the internal olefin sulfonate to the content of the hydroxyl in the internal olefin sulfonate in the component (c1) (olefin / hydroxyl) may be 0 / 100 or more, further 5 / 95 or more, and 50 / 50 or less, further 40 / 60 or less, further 30 / 70 or less, further 25 / 75 or less, from the viewpoint of suppressing wrinkle formation during drying.
[0074] The mass ratio of the content of the hydroxy form of the internal olefin sulfonate to the content of the olefin form of the internal olefin sulfonate in the component (c1) can be measured from the component (c1) by HPLC-MS.
[0075] The component (c1) can be produced, for example, by sulfonating, neutralizing, and hydrolyzing an internal olefin having 18 carbon atoms as a raw material. The sulfonation reaction can be carried out by reacting 1.0 to 1.2 moles of sulfur trioxide gas with 1 mole of the internal olefin. The reaction temperature can be 20 to 40°C. Neutralization is carried out by reacting with an aqueous alkali solution such as potassium hydroxide, ammonia, 2-aminoethanol, etc., in an amount 1.0 to 1.5 times the molar amount of the theoretical sulfonic acid group. The hydrolysis reaction may be carried out in the presence of water at 90 to 200°C for 30 minutes to 3 hours. These reactions can be carried out continuously. After the reaction is completed, the product can be purified by extraction, washing, etc.
[0076] In the present invention, the internal olefin refers to an olefin having a double bond inside the olefin chain, as described above.
[0077] <(c2) component> The component (c2) is a compound represented by the following general formula (c2). R 1c -B-SO3M (c2) [In formula (c2), R 1crepresents an alkyl group having 9 to 21 carbon atoms, B represents a benzene ring, and R bonded to the carbon atom of B 1c The carbon atom of is a secondary carbon atom, and M represents a hydrogen atom, an alkali metal, an alkaline earth metal (1 / 2 atom), ammonium or an organic ammonium. 1c In contrast, the sulfonic acid group is bonded to the ortho, meta or para position.
[0078] From the viewpoint of suppressing wrinkle formation during drying, R 1c is an alkyl group having 9 or more carbon atoms, preferably 10 or more, more preferably 11 or more, and preferably 18 or less, more preferably 16 or less, and even more preferably 14 or less. In the general formula (c2), M is preferably a hydrogen atom, an alkali metal such as sodium or potassium, an alkaline earth metal (1 / 2 atom) such as magnesium or calcium, or an organic ammonium from the viewpoint of suppressing wrinkle formation during drying. The organic ammonium salt may be a salt with an amine used in the pH adjuster. From the viewpoint of suppressing wrinkle formation during drying, M is more preferably an alkali metal such as sodium or potassium, an alkanol ammonium such as monoethanol ammonium or diethanol ammonium, and even more preferably sodium.
[0079] <(c3) component> The component (c3) is a compound represented by the following general formula (c3). R 2c -O-[(PO) m (EO) n ]-SO3M (c3) [In formula (c3), R 2crepresents an alkyl group having 8 to 22 carbon atoms, the carbon atom bonded to the oxygen atom is the first carbon atom, PO represents a propyleneoxy group, EO represents an ethyleneoxy group, EO and PO are block-type bonds or random-type bonds, the order of bonding between PO and EO does not matter, m and n represent the average number of moles added, m is 0 to 5 and n is 0 to 16, and M represents a hydrogen atom, an alkali metal, an alkaline earth metal (1 / 2 atom), ammonium or an organic ammonium.
[0080] From the viewpoint of suppressing wrinkle formation during drying, R 2c R is preferably an alkyl group having 9 or more carbon atoms, more preferably 10 or more, even more preferably 12 or more, and preferably 18 or less, more preferably 16 or less, even more preferably 14 or less. 2c is preferably a straight chain alkyl group. From the viewpoint of suppressing wrinkle formation during drying, in general formula (c3), m is preferably 4 or less, more preferably 3 or less, and further preferably 2 or less, and is 0 or more. From the viewpoint of suppressing wrinkle formation during drying, in general formula (c3), n is preferably 0.5 or more, more preferably 1 or more, even more preferably 2 or more, and is preferably 10 or less, more preferably 5 or less, even more preferably 4 or less. From the viewpoint of suppressing wrinkle formation during drying, M in the general formula (c3) is preferably a hydrogen atom, an alkali metal such as sodium or potassium, an alkaline earth metal (1 / 2 atom) such as magnesium or calcium, or an organic ammonium. The organic ammonium salt may be a salt with an amine used in the pH adjuster. From the viewpoint of suppressing wrinkle formation during drying, M is more preferably an alkali metal such as sodium or potassium, an alkanol ammonium such as monoethanol ammonium or diethanol ammonium, and even more preferably sodium.
[0081] From the viewpoint of suppressing wrinkle formation during drying, the component (c3) is preferably a polyoxyalkylene alkyl ether sulfate sodium salt in which the alkyl group has a carbon number of 12 to 14, the average number of moles of propyleneoxy groups added is 0 to 4, and the average number of moles of ethyleneoxy groups added is 1 to 4. That is, from the viewpoint of suppressing wrinkle formation during drying, the component (c3) is preferably a polyoxyalkylene alkyl ether sulfate sodium salt in which the alkyl group has a carbon number of 12 to 14, the average number of moles of propyleneoxy groups added is 0 to 4, and the average number of moles of ethyleneoxy groups added is 1 to 4. 2c is an alkyl group having 12 to 14 carbon atoms, m is 0 to 4, n is 1 to 4, and M is sodium.
[0082] <(c4) component> The component (c4) is a compound represented by the following general formula (c4). R 3c -CH(SO3M)COOR 4c (c4) [In formula (c4), R 3c represents an alkyl group having 6 to 20 carbon atoms, and R 4c represents an alkyl group having 1 to 6 carbon atoms, and M represents a hydrogen atom, an alkali metal, an alkaline earth metal (1 / 2 atom), ammonium, or an organic ammonium.
[0083] From the viewpoint of suppressing wrinkle formation during drying, R 3c represents an alkyl group having preferably 8 or more, more preferably 10 or more, and preferably 18 or less, more preferably 16 or less, carbon atoms. From the viewpoint of suppressing wrinkle formation during drying, R 4c represents an alkyl group preferably having 1 or more carbon atoms and preferably 5 or less, more preferably 4 or less. From the viewpoint of suppressing wrinkle formation during drying, M in the general formula (c4) is preferably a hydrogen atom, an alkali metal such as sodium or potassium, an alkaline earth metal (1 / 2 atom) such as magnesium or calcium, or an organic ammonium salt. The organic ammonium salt may be a salt with an amine used in the pH adjuster. From the viewpoint of suppressing wrinkle formation during drying, M is more preferably an alkali metal such as sodium or potassium, an alkanol ammonium such as monoethanol ammonium or diethanol ammonium, and even more preferably sodium.
[0084] The textile product treatment composition of the present invention contains component (c) in an amount of preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 5% by mass or more from the viewpoint of inhibiting wrinkle formation during drying, and in an amount of preferably 50% by mass or less, more preferably 25% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less from the viewpoint of defoaming property.
[0085] In the textile product treatment composition of the present invention, the mass ratio (a) / (c) of the content of the component (a) to the content of the component (c) is preferably 0.01 or more, more preferably 0.1 or more, from the viewpoint of defoaming property, and is preferably 20 or less, more preferably 10 or less, even more preferably 5 or less, and still more preferably less than 1, from the viewpoint of suppressing wrinkle formation during drying.
[0086] <(x) component> The textile product treatment composition of the present invention may optionally contain a surfactant other than components (a) and (c) [hereinafter referred to as component (x)] from the viewpoints of defoaming properties and suppression of wrinkle formation during drying. The component (x) includes one or more surfactants selected from nonionic surfactants, cationic surfactants, and amphoteric surfactants.
[0087] Examples of the nonionic surfactant of the component (x), from the viewpoints of anti-foaming properties and suppression of wrinkle formation during drying, include polyethylene glycol-type nonionic surfactants such as polyoxyalkylene alkyl or alkenyl ethers, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbit fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyoxyethylene alkyl phenyl ethers, and polyoxyalkylene (hydrogenated) castor oil; polyhydric alcohol-type nonionic surfactants such as sucrose fatty acid esters, polyglycerin alkyl ethers, polyglycerin fatty acid esters, and alkyl glycosides; and fatty acid alkanolamides.
[0088] From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, examples of the nonionic surfactant of the component (x) include nonionic surfactants represented by the following general formula (x1). R 1x (CO) m O-(AO) n -R 2x (x1) [In the formula, R 1x is an aliphatic hydrocarbon group having 9 to 18 carbon atoms, R 2x is a hydrogen atom or a methyl group, CO is a carbonyl group, m is a number of 0 or 1, AO groups are one or more groups selected from an ethyleneoxy group and a propyleneoxy group, and n is the average number of moles added, which is a number of 1 to 70.
[0089] In general formula (x1), R 1x is an aliphatic hydrocarbon group having 9 to 18 carbon atoms. From the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, R 1x has 9 or more, preferably 10 or more, more preferably 12 or more, and 18 or less, preferably 16 or less, more preferably 14 or less. R 1x The aliphatic hydrocarbon group is preferably a group selected from an alkyl group and an alkenyl group. In terms of antifoaming properties and suppression of wrinkle formation during drying, m in general formula (x1) is preferably 0. From the viewpoint of antifoaming properties and suppression of wrinkle formation during drying, R 2x is preferably a hydrogen atom.
[0090] In the general formula (x1), the AO group is one or more groups selected from an ethyleneoxy group and a propyleneoxy group. When the ethyleneoxy group and the propyleneoxy group are contained, the ethyleneoxy group and the propyleneoxy group may be a block type bond or a random type bond. From the viewpoint of antifoaming property and suppression of wrinkle formation during drying, the AO group is preferably a group containing an ethyleneoxy group. In addition, the order of bonding of the ethyleneoxy group and the propyleneoxy group does not matter.
[0091] In the general formula (x1), n is the average number of moles added and is a number from 1 to 70. From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, n is 1 or more, preferably 5 or more, more preferably 10 or more, and 70 or less, preferably 60 or less, more preferably 50 or less, even more preferably 40 or less, still more preferably 30 or less, and even more preferably 25 or less.
[0092] From the viewpoint of antifoaming properties and inhibition of wrinkle formation during drying, more preferred compounds as the nonionic surfactant of component (x) are those in which the average degree of polymerization (also referred to as the average number of moles added) of ethyleneoxy groups (hereinafter sometimes referred to as EO groups) is 1 or more, preferably 5 or more, more preferably 10 or more, and 70 or less, preferably 50 or less, and even more preferably 25 or less, and the average degree of polymerization (also referred to as the average number of moles added) of propyleneoxy groups (hereinafter sometimes referred to as PO groups) is 0 or more and 5 or less, preferably 4 or less, and the EO groups and the PO groups are bonded in a block or random manner, preferably in a block manner, and more preferably in which the EO groups and the PO groups are bonded in a block or random ... 1x and the alkyl group is derived from a linear primary or secondary alcohol having 12 to 18 carbon atoms, more preferably 12 or 14, and even more preferably 12 carbon atoms.
[0093] Examples of the cationic surfactant of the component (x) include cationic surfactants which are tertiary amine salts and cationic surfactants which are quaternary ammonium salts, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0094] Examples of the amphoteric surfactant of the component (x) include betaine-based amphoteric surfactants and amine oxide-type amphoteric surfactants, from the viewpoints of antifoaming properties and suppression of wrinkle formation during drying.
[0095] When the textile product treatment composition of the present invention contains component (x), from the viewpoints of defoaming properties and suppression of wrinkle formation during drying, the composition contains component (x) in an amount of preferably 0.01 mass % or more, more preferably 0.1 mass % or more, even more preferably 1 mass % or more, still more preferably 5 mass % or more, and preferably 50 mass % or less, more preferably 25 mass % or less, and even more preferably 15 mass % or less.
[0096] In the textile product treatment composition of the present invention, the ratio of the total amount of the (a) component and the (c) component to the total amount of the surfactant is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, and preferably 100% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, even more preferably 70% by mass or less, even more preferably 60% by mass or less, and even more preferably 50% by mass or less, from the viewpoint of defoaming properties and suppression of wrinkle formation during drying. The total amount of the surfactant may be the total content of the (a) component, the (c) component, and the (x) component in the composition. The textile product treatment composition of the present invention may be a composition containing a surfactant, containing the (a) component and the (c) component as the surfactant in the above-mentioned predetermined ratio, and the ratio of the total content of the (a) component and the (c) component to the content of the surfactant may be in the above-mentioned range.
[0097] From the viewpoint of defoaming properties and suppression of wrinkle formation during drying, the textile product treatment composition of the present invention may contain, as optional components other than component (a) and component (b), for example, a pH adjuster, a fragrance, an antibacterial agent such as diclosan, a bleaching agent, a bleaching activator, a defoaming agent, a fragrance capsule, an enzyme, a silicone, etc.
[0098] The textile product treatment composition of the present invention preferably contains water from the viewpoint of antifoaming properties and wrinkle formation inhibition during drying. The textile product treatment composition of the present invention may be a liquid composition containing water. The water is preferably water that does not contain impurities and is moderately purified. Well water and industrial water can also be used. The water is preferably tap water, purified water, or ion-exchanged water from the viewpoint of antifoaming properties and wrinkle formation inhibition during drying. The textile product treatment composition of the present invention preferably contains water in an amount of 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and preferably 95% by mass or less, preferably 90% by mass or less, and more preferably 85% by mass or less from the viewpoint of antifoaming properties and wrinkle formation inhibition during drying. The content of water may be the remainder of the total content of the (a) component, the (b) component, and any optional components.
[0099] The textile product treatment composition of the present invention has a pH at 25°C, measured by the following method, of preferably 4 or more, more preferably 5 or more, and preferably 12 or less, more preferably 11 or less, from the viewpoints of defoaming properties and inhibition of wrinkle formation during drying. [pH measurement method] A composite electrode for pH measurement (glass-ground sleeve type, manufactured by HORIBA) is connected to a pH meter (pH / ion meter F-23, manufactured by HORIBA) and the power is turned on. A saturated aqueous potassium chloride solution (3.33 mol / L) is used as the internal solution of the pH electrode. Next, a 100 mL beaker is filled with a pH 4.01 standard solution (phthalate standard solution), a pH 6.86 standard solution (neutral phosphate standard solution), and a pH 9.18 standard solution (borate standard solution), and the beaker is immersed in a thermostatic bath at 25°C for 30 minutes. The pH measurement electrode is immersed in the thermostatically adjusted standard solution for 3 minutes, and a calibration operation is performed in the order of pH 6.86 → pH 9.18 → pH 4.01. The sample to be measured (textile product treatment composition of the present invention) is adjusted to 25°C, the electrode of the pH meter is immersed in the sample, and the pH is measured after 1 minute.
[0100] The textile product treatment composition of the present invention can be used for various fibers, such as natural fibers, synthetic fibers, and semi-synthetic fibers. The textile product treatment composition of the present invention can be used for textile products containing these fibers. Examples of natural fibers include cotton and hemp, and examples of synthetic fibers include polyester fibers. In the present invention, the textile product means fabrics such as woven fabrics, knitted fabrics, nonwoven fabrics, etc. using these various fibers, and textile products obtained using them, for example, products such as undershirts, T-shirts, dress shirts, hats, handkerchiefs, towels, masks, etc. Preferred textile products are woven fabrics such as woven fabrics and knitted fabrics, and woven textile products.
[0101] <Method of processing textile products> The method for treating textile products of the present invention comprises treating the textile products with a treatment liquid obtained by mixing component (a), component (b) and water, and then drying the textile products. The pH of the treatment liquid during use, and further the pH of the treatment liquid at 25°C, may be in the same range as the pH range described for the textile product treatment composition of the present invention. The treatment liquid may also optionally contain the above-mentioned component (c) and component (x). The textile product can be treated (washed) and dried in accordance with a known method. The method for treating a textile product of the present invention may be a method for treating a textile product, which comprises treating the textile product with a treatment liquid comprising a mixture of the textile product treatment composition of the present invention and water, and then drying the textile product. The method for treating a textile product of the present invention may be a method for washing a textile product, which comprises washing the textile product with a cleaning liquid comprising a mixture of the textile product treatment composition of the present invention and water, and then drying the textile product. In the textile product treatment method of the present invention, the textile product may be dried naturally or in a dryer. From the viewpoint of suppressing wrinkle formation during drying, it is preferable to dry the textile product in a dryer. Drying in a dryer also includes drying the textile product using the drying function of a washing machine. In the method for treating a textile product of the present invention, after treating the textile product with the treatment liquid or cleaning liquid, the textile product may be rinsed with water and / or dehydrated, and then dried. The rinsing and dehydration of the textile product may be performed according to a known method. The matters described in relation to the textile product treatment composition of the present invention can be appropriately applied to the textile product treatment method of the present invention. Specific examples and preferred embodiments of the components (a) and (b), optional components, and preferred mass ratios of the components in the textile product treatment method of the present invention are also the same as those of the textile product treatment composition of the present invention.
[0102] The concentration of the (a) component in the treatment liquid (including the cleaning liquid, the same applies hereinafter) is preferably 0.0001 mass % or more, more preferably 0.0005 mass % or more, from the viewpoint of defoaming property, and is preferably 10 mass % or less, more preferably 1 mass % or less, from the viewpoint of suppressing wrinkle formation during drying.
[0103] The treatment liquid is preferably prepared by diluting the textile product treatment composition of the present invention with water so that the content of component (a) falls within the above range. The specific dilution ratio is preferably 500 times or more, more preferably 800 times or more, and preferably 5,000 times or less, more preferably 3,000 times or less, from the viewpoints of defoaming properties and suppression of wrinkle formation during drying.
[0104] From the viewpoints of antifoaming properties and suppression of wrinkle formation during drying, the concentration of component (b) in the treatment liquid is preferably 0.00001 mass % or more, more preferably 0.0001 mass % or more, and preferably 1 mass % or less, more preferably 0.1 mass % or less, and even more preferably 0.01 mass % or less.
[0105] From the viewpoint of suppressing wrinkle formation during drying, the concentration of the component (c) in the treatment liquid is preferably 0.0001% by mass or more, more preferably 0.0005% by mass or more, and preferably 10% by mass or less, more preferably 1% by mass or less.
[0106] The textile product treatment method of the present invention can be carried out using, for example, a home washing machine or a commercial washing machine. The conditions therefor can be the temperature, time, bath ratio, etc. that are usually used. The textile product treatment method of the present invention can reduce the foaming property of the treatment liquid when treating the textile product. In addition, it can reduce wrinkles formed on the textile product when drying the textile product, particularly when drying the textile product with a dryer. EXAMPLES
[0107] (1) Ingredients The components used in the examples and comparative examples are shown below. <Component (a)> (a-1) Sodium di-2-ethylhexyl sulfosuccinate (a-2) Sodium di-2-propylheptyl sulfosuccinate <(b) Component> (b1-1) AC-HEC: alkylated cationized hydroxyethyl cellulose, alkyl introduction amount 0.02, cationic group introduction amount 0.10, molecular weight 150,000 (b1-2) C-HEC: cationized hydroxyethyl cellulose, Poise C-60H (Kao Corporation), molecular weight 600,000, cationic group introduction amount 0.40 (b1-3) C-HEC: cationized hydroxyethyl cellulose, Poise C-150L (Kao Corporation), molecular weight 1.5 million, cationic group introduction amount 0.25 (b1-4) Vinyl cationic polymer: N,N-dimethylaminoethyl methacrylate diethyl sulfate·N,N-dimethylacrylamide·polyethylene glycol dimethacrylate / polyoxyethylene lauryl ether (16), SOFCARE KG-101W-E (Kao Corporation), cationic group introduction amount 0.10 (b2) A-HEC: alkylated hydroxyethyl cellulose, molecular weight 150,000, alkyl introduction amount 0.02 <(b') component> (b') Anionic polymer (dispersant): polyacrylic acid copolymer, AQUALIC (manufactured by Nippon Shokubai Co., Ltd.) <(c) component> (c1) C18IOS: Potassium salt of an internal olefin sulfonate having 18 carbon atoms. The mass ratio of the olefin form (potassium olefin sulfonate) / hydroxy form (potassium hydroxyalkanesulfonate) in the C18IOS is 16 / 84. The mass ratio of the positional distribution of sulfonic acid groups of the HAS form in the C18IOS is as follows: 1st position / 2nd position / 3rd position / 4th position / 5th position / 6th to 9th position=1.5 / 22.1 / 17.2 / 21.8 / 13.5 / 23.9. In addition, (IO-1S) / (IO-2S)=1.6 (mass ratio). (c2) LAS: sodium alkylbenzenesulfonate (alkyl composition: C10 / C11 / C12 / C13 = 11 / 29 / 34 / 26 (mass ratio), mass average carbon number of the whole compound = 17.75) (c3-1) AES: Polyoxyethylene (3) lauryl ether sodium sulfate (EMAL 20C, manufactured by Kao Corporation) (c3-2) APES: (polyoxypropylene) polyoxyethylene lauryl ether sulfate sodium salt in which the alkyl group is derived from lauryl alcohol, the average number of moles of propyleneoxy groups added is 2 moles, and the average number of moles of ethyleneoxy groups added is 2 moles. <Nonionic surfactants (standard)> C12 / 14(EO)10: Polyoxyethylene mixed alkyl ether (a polyoxyethylene group is bonded to a mixed alkyl group of alkyl group having 12 carbon atoms / alkyl group having 14 carbon atoms (7 / 3, mass ratio), and the average number of moles of oxyethylene groups added is 10 moles.)
[0108] (2) Preparation of textile product treatment composition A 5 cm long Teflon (registered trademark) stirrer piece was placed in a 100 mL glass beaker and the mass was measured. Next, the (c) component, the (a) component, and the (b) component (or (b')) were placed in this order in the proportions shown in Table 1, and 5 g of ion-exchanged water was added and the top of the beaker was sealed with Saran Wrap (registered trademark). The beaker containing the contents was placed in a 60°C water bath installed on a magnetic stirrer, and the temperature of the water in the water bath was within a temperature range of 60±2°C and stirred at 100 r / min for 30 minutes. Next, the water in the water bath was replaced with tap water at 5°C, and the composition in the beaker was cooled to a temperature of 20°C and then stirred for 10 minutes. Next, the Saran Wrap (registered trademark) was removed, ion-exchanged water was added so that the mass of the contents was 100 g, and the mixture was stirred again at 100 r / min for 5 minutes to obtain the textile product treatment composition shown in Table 1.
[0109] (3) Pretreatment of textile products (3-1) Pretreatment of clothing fabric In advance, about 1.6 kg of commercially available underwear (Gunze Ltd. YG underwear, 100% cotton, size L) was washed five times in a Panasonic NA-F70PB1 fully automatic washing machine using a nonionic surfactant (ethylene oxide adduct of lauryl alcohol (average number of moles added: 8)) (amount of nonionic surfactant used: 4.5 g, standard course, water volume: 45 L, water temperature: 25°C, washing time: 12 minutes, rinse twice). Then, it was dried for one day under the conditions of 25°C and 43% RH.
[0110] (3-2) Pretreatment of cotton T-shirts In advance, a nonionic surfactant (ethylene oxide adduct of lauryl alcohol (average number of moles added: 8)) was used to wash 10 pieces of commercially available T-shirts (UNIQLO crew neck T-shirts (M), 100% cotton) in a Panasonic NA-F70PB1 fully automatic washing machine five times in a row (amount of nonionic surfactant used: 4.5 g, standard course, water volume: 45 L, water temperature: 25°C, washing time: 10 minutes, rinse twice). After that, the T-shirts were dried for one day under conditions of 25°C and 43% RH.
[0111] (4) Washing of evaluated fibers 15 g of the textile product treatment composition in Table 1 was weighed out, and three cotton T-shirts pretreated as described above were washed in a drum-type washer / dryer (Panasonic NA-VX3800L) with tap water (25°C) and a total weight of 4 kg of clothing under the standard cycle (25 L of water (actual value), 15 minutes of washing, one rinse, and automatic spin / dry settings). Underwear, which is a garment conditioning fabric pretreated as described above, was used to adjust the weight of the clothing. After the drying process was completed, the cotton T-shirts were removed from the washing machine and the appearance of the cotton T-shirts was evaluated.
[0112] (5) Evaluation of anti-wrinkle ability The wrinkle state of the T-shirts that had been washed, rinsed, and dried using the method described in (4) above was scored by six experts in the texture evaluation of textile products using the following criteria, and the average score of the six people was calculated. The results are shown in Table 1. The values shown in the table have been rounded off to one decimal place. In this evaluation, it is preferable for the average score to be 1 or higher, and the higher the number, the better. -1: More wrinkles were observed than in the T-shirt treated with the composition of Comparative Example 1. 0: The wrinkles were the same as those of the T-shirt treated with the composition of Comparative Example 1. 1: Compared with the T-shirt treated with the composition of Comparative Example 1, the finished product had slightly fewer wrinkles. 2: Compared with the T-shirt treated with the composition of Comparative Example 1, the finished product had fewer wrinkles. 3: Compared with the T-shirt treated with the composition of Comparative Example 1, the finished product had significantly fewer wrinkles.
[0113] (6) Evaluation of the defoaming properties of the treatment solution <How to prepare hard water> Hard water (Ca / Mg=8:2 (mass ratio)) was prepared by the following method. Calcium chloride dihydrate (FUJIFILM Wako Pure Chemical Industries, Ltd.) and magnesium chloride hexahydrate (FUJIFILM Wako Pure Chemical Industries, Ltd.) were weighed out in amounts equivalent to a German hardness of 150°DH so that the calcium ion / magnesium ion ratio (molar ratio) was 8 / 2, and the weighed compounds were dissolved in ion-exchanged water at 20°C to prepare a concentrated stock solution. This concentrated stock solution was diluted 100 times with ion-exchanged water and adjusted to 5°C to prepare hardness water.
[0114] <Method of measuring water hardness in Germany> The German hardness was measured by the following method. 〔reagent〕 0.01 mol / L EDTA·2Na solution: 0.01 mol / L aqueous solution of disodium ethylenediaminetetraacetate (titration solution, 0.01M EDTA-Na2, manufactured by Sigma-Aldrich) Universal BT indicator (product name: UniversalBT, manufactured by Dojindo Laboratories, Ltd.) Ammonia buffer solution for hardness measurement (67.5 g of ammonium chloride dissolved in 570 ml of 28 w / v% ammonia water, and then made up to 1000 ml with ion-exchanged water) [Method of measuring hardness] First, 20 mL of sample water was collected in a conical beaker using a whole pipette, and 2 mL of ammonia buffer solution for hardness measurement was added. Furthermore, 0.5 mL of Universal BT indicator was added, and it was confirmed that the solution after addition was reddish purple. While shaking the conical beaker well, 0.01 mol / L EDT·2Na solution was dropped from the burette, and the end point of the titration was when the sample water turned blue. The total hardness in the sample was calculated from the titration volume T (mL) of the EDTA·2Na solution using the following formula. Hardness (°DH)=(T×0.01×F×56.0774×100) / A T:0.01mol / L Titration amount of EDTA・2Na solution (mL) A: Sample volume (20 mL, volume of sample water) F: Factor of 0.01mol / L EDTA·2Na solution
[0115] <Evaluation of antifoaming properties> 50 mL of each hard water prepared by the above hard water preparation method was placed in a screw tube (No. 8), and 0.05 g of the textile product treatment composition in Table 1 was measured and dropped into it to prepare a treatment liquid. The screw tube was then capped and shaken at 300 rpm for 3 minutes with a shaker (STRONGSHAKER SR-2DW, manufactured by TAITEC), and the foam height (cm) 30 seconds after shaking was measured with a ruler. The defoaming performance was calculated by the following formula based on the foam height of Comparative Example 1. The calculated defoaming performance value is less than 1.0, and the lower the value, the better the defoaming treatment liquid is. A treatment liquid with excellent defoaming performance can also be said to have excellent rinsing properties. In addition, if the calculated defoaming performance value is more than 0, it can be said that the generated foam is appropriately maintained. Defoaming performance = (foam height (cm) of the treatment liquid of the Example or Comparative Example) / (foam height (cm) of the standard treatment liquid)
[0116] [Table 1]
Claims
1. A textile product treatment composition comprising the following components (a) and (b): Component (a): a sulfosuccinate ester or a salt thereof having a hydrocarbon group having 5 to 18 carbon atoms Component (b): one or more polymers selected from the following components (b1) and (b2): Component (b1): cationic polymer Component (b2): nonionic polymer
2. 2. The textile product treatment composition according to claim 1, which is a wrinkle inhibitor for textile products that inhibits wrinkles from forming on textile products during drying.
3. The textile product treatment composition according to claim 1, which is a detergent composition for textile products.
4. The fiber product treatment composition according to claim 1, wherein the component (b1) is a polysaccharide polymer having a cationic group.
5. The textile product treatment composition according to claim 1, further comprising the following component (c): Component (c): Anionic surfactant
6. 6. The fiber product treatment composition according to claim 5, wherein the mass ratio (a) / (c) of the content of the component (a) to the content of the component (c) is less than 1.
7. A method for treating a textile product, comprising treating the textile product with a treatment liquid obtained by mixing the following components (a) and (b) and water, and then drying the textile product: Component (a): a sulfosuccinate ester or a salt thereof having a hydrocarbon group having 5 to 18 carbon atoms Component (b): one or more polymers selected from the following components (b1) and (b2): Component (b1): cationic polymer Component (b2): nonionic polymer
8. The method for treating a textile product according to claim 7, wherein the textile product is treated with a treatment liquid comprising a mixture of the textile product treating composition according to any one of claims 1 to 6 and water.